(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: The microbial infections are major cause in abortion, of which viruses appear to be the most frequently involved pathogens. Human Herpes Virus-6 (HHV-6) has been implicated in cases of poor pregnancy outcome. Objective: Detection and quantification of HHV-6 viral load along with titer of IgM and IgG in endometrial epithelial cells of women with unexplained miscarriage (cases group) compared to the decidual endometrial tissue in women with full term conception (the control group). Methods: A total of 90 samples, 45 were taken by curettage from miscarriage women at first and second trimesters of pregnancy and 45 were taken from women with full term pregnancy during caesarian operation. HHV-6 DNA was extracted from uterus lining tissue samples, and then it was detected and measured by real time qPCR; in addition, 3 ml of blood were collected from each subject for detection of HHV-6 IgM and IgG antibodies. Results: HHV-6 DNA was detected in uterus lining tissue of 20% of abortion and 22.22% of controls (P value=0.79). The median viral load of HHV-6 per 106 of uterine cells in abortion group was 15, while for control group was 13 (P=0.54). HHV-6 load increased with increased number of previous abortions, and it increased with presence of recurrent abortion history. It showed significant differences in the median of HHV-6 DNA load between recurrent abortion and non-recurrent abortion groups (P value =0.033). Positive anti-HHV-6 IgM serum antibodies in HHV-6 DNA detected and no-detected subjects were 0%, and 9.85% respectively; the positive anti-HHV-6 IgG serum antibodies in detected HHV-6 DNA were 100%, while 83% in HHV-6 DNA non-detected subjects. The combination of positive/negative results of the anti-HHV-6 IgG and IgM serum antibodies in HHV-6 DNA detected versus non-detected group showed 100% of HHV-6 DNA detected were positive for IgG and negative for IgM, versus 73% in non-detected group. Conclusion: HHV-6 might associated with unexplained miscarriage. HHV-6 infection might increase with increased number of previous abortions, and increased with presence of recurrent abortion history. Keywords: Human Herpes Virus 6A, Miscarriage Citation: Dosh HS, Abdulamir AS, Abdul-Razzaq SH. Association of Human Herpes Virus 6A infection in endometrial epithelial cells with miscarriage. Iraqi JMS. 2019; 17(1): 57-65. doi: 10.22578/IJMS.17.1.9